Grass Flora of Pudukkottai District, Tamil Nadu, India - Raja, P.; Soosairaj, S.; Tagore, Johny Kumar; Althaf AhamedKabeer, K. (Indian Forester, 2021)
The present study deals with an account of grasses (Poaceae) collected from Pudukkottai district of Tamil Nadu, India. The study records 91 species under 56 genera and the most dominant genus is Eragrostis (7 species), Brachiaria, Panicum (5 species each). Besides twenty one (21) species were first time reported from Pudukkottai district. Three species are endemic to India, among them Chrysopogon hackelii and Iseilema anthephoroides are endemic to Peninsular India.